ЗАРИМ ЗҮЙЛ УРГАМАЛ ДАХЬ ТЭЖЭЭЛИЙН ЭЛЕМЕНТҮҮДИЙГ ТОДОРХОЙЛСОН ДҮН - Ганцэцэг, Д (Proceedings of the Mongolian Academy of Sciences, 2016)
The nutrients required to grow plant is only one aspect of successful crop production. The source of nutrients to use and how the elements influenced by soil , atmosphere and water. Although 16 nutrients elements required to grow plants, 13 of them are taken up from the soil. Global warming and climate changes possible impact on nutrient elements of plant tissue and time period of growing so samples which are dominant plants, were gathered by Mungun morit , Tumentsogt and Ikhnart sums in June to August. The samples was prepared for experiment as well as content of Mn , Ni, Pb ,Fe, Cd, Cu, Zn and Cr elements measured by AAS. By results of analysis, content of Iron in Potentilla acualis (in July) is higher than other elements as well as Cd and Pb are not out in all.